Motion Compensation in SAS with Multiple Receivers Based on ISCFT Imaging Algorithm - Huang Jinquan; Tang Jinsong; Wang Qin; Wu Wenquan (2010 2nd International Conference on Information Engineering and Computer Science, 2010)
Synthetic Aperture Sonar (SAS) performance is limited by motion errors of the towfish. It is necessary to require the towfish moving in a straight line in order to improve the imaging efficiency by Fast Fourier Transformation (FFT). However, the towfish could hardly move along a straight line because of some factors such as ocean wave, ocean current and tide. All kinds of motion errors could incur phase error in echo signal and make the quality of final image decline. The aim of this work is to lighten the influence of the motion errors in final image. Motion errors of towfish are analyzed in detail and a motion compensation (MOCO) scheme based on Inverse Scaled Fourier Transformation (ISCFT) imaging algorithm is proposed.The simulation trials validate the analysis and the scheme.